Local recurrence of breast cancer: Salvage lumpectomy as an option for local treatment. Issue 4 (13th May 2019) - Sellam, Yael; Shahadi, Ilanit D.; Gelernter, Ilana; Zippel, Douglas; Sklair‐Levy, Miri; Symon, Zvi; Galper, Shira; Ben‐David, Merav A.
Abstract: Introduction: The best local management for breast cancer recurrence following conservative treatment for breast cancer (BC) continues to be an open question. In this study, we compared patients' outcome after salvage lumpectomy (SL) vs mastectomy for ipsilateral breast tumor recurrence (IBTR). Materials and methods: Between 1987 and 2014 we identified 121 patients with pT0‐2, N0‐3, M0 BC who had BCT as their primary treatment, and subsequently had IBTR (unifocal). 47 patients underwent SL and 74 salvage mastectomy (SM) as the local treatment for their 1st recurrence. Results: Median follow‐up was 14 years (1‐30) from first BC diagnosis. For the SL and SM cohorts, 8 and 10 patients (17%, 13.5%, P  = 0.22), respectively, developed subsequent local recurrence as a 3rd event. Although in MVA, woman who underwent SL had higher chances of having a 2nd recurrence (3rd event), P  = 0.020, at a median follow‐up of 14 years, 95.8% of SL patients are alive, NED, 85% are mastectomy free. 87% of patients who opted for SM are alive, NED. Having re‐irradiation following SL did not protect against 2nd breast cancer recurrence (3rd event, P  = 0.42). Conclusion: Salvage lumpectomy following IBTR, while associated with higher second LR rate than SM is not associated with inferior outcome. With survival >95% at 14 years in the SL cohort, salvage lumpectomy with or without re‐radiation, in a selected population (unifocal T), represents an acceptable treatment option for patients in order to delay time to mastectomy without reducing BC survival. Both options should be discussed prior to any surgical decision.